Contextualizing parasympathetic hyperactivity in functionally overreached athletes with perceptions of training tolerance - Bellenger, C. R.; Karavirta, L.; Thomson, R. L.; Robertson, E. Y.; Davison, K.; Buckley, J. D. (International Journal of Sports Physiology and Performance, 2016)
Purpose: